Factors influencing the intention to perform cash waqf among Muslim staff at Universiti Teknologi MARA, Kelantan Campus - Yusoff, Ruslaina; Abd Rahman, Shariful Amran; Wan Mohamed, Wan Nazihah (Universiti Teknologi MARA, Kelantan, 2018)
Cash waqf is one of the instruments of charitable conduct in Islamic religious and has been perceived as a method for waqf practice. The aim of this study is to identify factors that influence the goal to perform cash waqf among Muslim, particularly university staff. A survey with a seven-point scale was utilized to gather the information for the present study and items from past researches were modified to suit cash waqf setting. The survey was disseminated to 692 staff of Universiti Teknologi MARA Kelantan Campus, Malaysia. The response rate was 36.6 percent (253 samples). The outcome from the information gathered proposed that all three factors (attitude, subjective norm & perceived behavioral control) have significant association with the expectation to perform cash waqf. Hence, all three factors were able to explain the intention to perform cash waqf.